Pattern of neurosurgical cases and procedures in Gilgit Baltistan: two-year experience at a newly established neurosurgical department. Issue 5 (20th October 2022) - Farhan, Muhammad; Alam, Sudhair; Zulqarnain, Iqra; Haider, Tehseen; Basit, Jawad; Imran, Muhammad; Rehman, Mohammad Ebad Ur; Saeed, Sajeel; Arish, Muhammad; Lee, Ka Yiu
ABSTRACT: Background: In Pakistan, there are a total of 160 neurosurgeons that constitute a ratio of one neurosurgeon for a 5.5 million population. Gilgit Baltistan being a backward region does not have a single tertiary care facility. A new department of neurosurgery was established at Regional Headquarter City Hospital (RHQ) Gilgit with only one neurosurgeon. This study aimed to determine which neurosurgical diagnoses are common and which surgical interventions were performed at RHQ. Methods: This is a retrospective cross-sectional study conducted at Regional Headquarter Hospital (RHQ) Gilgit in which data of patients operated for neurosurgical diseases between January 2020 and January 2022 was collected from patient record books. Results: Of the total of 223 patients, 148 (66.3%) were males and 75 (33.6%) were females. A total of 92(41.2%) belonged to the pediatric age group. The top most diagnosis included Neurotrauma (46.6%), NTDs (13.9%) and CSDH (10.3%) while the most routinely performed procedures were craniotomy & hematoma evacuation (22.9%), debridement & elevation of DSF (20.6%), and burrhole evacuation (13.9%). In the pediatric age group, the top diagnosis was Neurotrauma (43.5%), NTDs (32.6%), and Hydrocephalus (19.6%) while in adults, neurotrauma (48.9%) was the leading diagnosis followed by CSDH (17.6%). In the pediatric age group, repair of NTDs (32.6%) was the most frequently performed procedure. Conclusion: This study shows different kinds of neurosurgical cases but because of a lack of diagnostic and therapeutic facilities, very limited operations were performed and many cases were referred to metropolitan cities. The hospitals in the region need further up-gradation to cater to the presenting burden.